2019
DOI: 10.5194/bg-2019-93
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Warming enhances carbon dioxide and methane fluxes from Red Sea seagrass (<i>Halophila stipulacea</i>) sediments

Abstract: <p><strong>Abstract.</strong> Seagrass meadows are autotrophic ecosystems storing carbon in their biomass and sediments, but they have also been shown to be sources of carbon dioxide (CO<sub>2</sub>) and methane (CH<sub>4</sub>). Seagrasses can be negatively affected by increasing seawater temperatures, but the effects of warming on CO<sub>2</sub> and CH<sub>4</sub&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The replacement of climax seagrass species, generally characterized by high biomass and productivity, by pioneer species will also decrease the capacity of seagrass meadows to mitigate the effects of carbon emissions (Gattuso et al 2018). Under some warming scenarios, seagrasses ecosystem may even switch metabolism from autotrophic to heterotrophic (Burkholz et al 2019), and enhance CO2 and methane fluxes from the meadows into the atmosphere (Burkholz et al 2020).…”
Section: Difference Between Climax Versus Pioneer Seagrasses In Respo...mentioning
confidence: 99%
“…The replacement of climax seagrass species, generally characterized by high biomass and productivity, by pioneer species will also decrease the capacity of seagrass meadows to mitigate the effects of carbon emissions (Gattuso et al 2018). Under some warming scenarios, seagrasses ecosystem may even switch metabolism from autotrophic to heterotrophic (Burkholz et al 2019), and enhance CO2 and methane fluxes from the meadows into the atmosphere (Burkholz et al 2020).…”
Section: Difference Between Climax Versus Pioneer Seagrasses In Respo...mentioning
confidence: 99%
“…How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, ; Barber & Carlson, ; Deborde et al, ; Garcias‐Bonet & Duarte, ; Oremland, ). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon‐Durocher, Hulatt, Woodward, & Trimmer, ; Yvon‐Durocher, Montoya, Woodward, Jones, & Trimmer, ), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias‐Bonet, & Duarte, ; Lyimo et al, ), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias‐Bonet & Duarte, ). In general, the methane production of biological systems is closely correlated with the productivity of the plants within the system (Borges, Speeckaert, Champenois, Scranton, & Gypens, ; Bridgham et al, ), and for wetlands in particular, there is a clear positive correlation between emission of methane and net ecosystem production (Whiting & Chanton, ).…”
Section: Introductionmentioning
confidence: 99%